Development of 3D tethered particle motion as a tool to study conformational changes of biomolecules - Chan, Nicholas Zhen Woon (2018)
Tethered particle motion is a simple yet powerful technique that allows researchers to study various protein-DNA interactions. By non-specifically anchoring a DNA onto the glass coverslip and attaching a fluorescent bead to the other end of the DNA through a biotin-avidin interaction, scientist have been able to probe conformational changes of the tether through observation of the Brownian motion of the bead. In this Project, we will attempt to track the Brownian motion of the reporter bead over a period of time so as to obtain the relationship between the length of the tethered DNA and the root-mean-square (RMS) excursion value of the bead. We will also go one step further by extending the range of observance from 2-Dimensional tracking into 3-Dimensional tracking through the introduction of a weak cylindrical lens and the concept of Astigmatism.